A Novel Material Identification Method Based on Material Surface Static Electricity Discharge - Licheng ZHU; Pengfei LI; Kai LIU; Xi CHEN; Gengchen SHI (Medžiagotyra, 2017)
In this paper, a novel material identification method is introduced based on material surface static electricity discharge. Firstly, the induced charge model between charged material and metal electrode is established. Simulation results verified that the change of induced charge was influenced by the degree of the material surface static electricity discharge. Next, the electrostatic signal acquisition system with a special structure was designed and presented. Subsequently, five typical indoor materials, aluminum, glass, paper, wood, and polytetrafluoroethylene (PTFE) were tested. The degree of discharge was defined by the discharge factor (α) and repeated experiments verified α as a stable parameter for materials with standard deviations below 4%. Moreover, α revealed good corresponding relationship with material resistivity. Consequently, the discharge factor can be regarded as a parameter for material identification and prove applicability in rapid detection as well as identification of materials. DOI: http://dx.doi.org/10.5755/j01.ms.23.4.16676